JEJAK SEJARAH DALAM SASTRA LISAN DI NUSANTARA - Muhammad Fadli Muslimin; Mira Utami (TELAGA BAHASA, 2020)
The oral literature had a close relation to history, where oral literature which is part of oral tradition become the main container in the delivery of historical facts. Therefore, tracking historical facts in oral literature in the archipelago. The purpose of this study is to reveal the historical traces that exist in oral traditions in Indonesia, especially those found in Bugis, Minangkabau, Sundanese, Banjar, Kerinci, and Sentani oral literature. The method used is the descriptive analysis utilizing the theory of Jan M. Vansina about oral tradition as history. The results of the research show that the historical content in oral literature tells about the origins of humans, the lives of the past kings, and their narrative tends to be personified.